Neuropsychiatric Symptoms in an Inpatient Parkinson’s Disease Sample - Nicole C. R. McLaughlin; Irene Piryatinsky; Gary Epstein-Lubow; Louis Marino; Joseph H. Friedman (Parkinson's Disease)
Background. Neuropsychiatric symptoms are common in idiopathic Parkinson’s disease (PD), and hospitalization for delirium, depression, psychosis, and anxiety is sometimes required. A minimal amount of data exists on these patients. Methods. Charts of all patients admitted to a psychiatric hospital between 2006 and 2009 with a diagnosis of PD were reviewed. Forty-three met entry criteria and were reviewed. Initial and discharge diagnoses, comorbid psychiatric diagnoses, length of stay, and living arrangements before and after hospitalization are described. Results. Consistent with previous research, this study showed evidence of comorbid psychiatric disorders within PD. Conclusions. The long-term goal of this area of study would be to reduce neuropsychiatric symptoms and improve quality of life in order to reduce inpatient hospital stays.